Socio-Economic Aspects of Community in Limboto Lake Management in Telaga Biru District, Gorontalo Regency - Muh. Firyal Akbar; Ramlah Alkatiri; Zulkifli Tuli (Newinera Publisher, 2022)
This research aims to determine the impact of Limboto Lake management in terms of the sosio-economic aspects of the coastal communities of the Lake, Telaga Biru District, Gorontalo regency. The research method uses a qualitative type. The results showed that Lake management was not optimal, this can be seen from the negative side effects of reduced livelihoods and income of fishing communities as well as the emergence of several diseases such as anthrax and respiratory problems due to decreased water quality and air quality. The positive impact determined by the program objectives is not clear, the ecological impact is not positive so that it can lead to undesirable things. The positive side effect can control the water discharge when Limboto Lake water overflows, then it can be used as a tourist spot so that people can open businesses such as shops, selling accessories and motorbike taxis or parking lots for visitors. However, this is only sporadic when there are big events.